Vision Restoration through transorbital electrical stimulation in Optic Neuropathy in patients with significant optic atrophy due to primary open-angle glaucoma—a randomised, controlled, double-blind, multicentre clinical trial: the VIRON study protocol - Katrin Lorenz; Alexander Radbruch; Hans Hoerauf; Philip Enders; Karl Mercieca; Christian van Oterendorp; Marc Brockmann; Anna Beck; Thomas Asendorf; Bettina Wabbels; Michael Schittkowski; Verena Prokosch; et al. (BMJ Open)
Introduction Glaucoma is one of the most common causes of blindness and affects more than 70 million people worldwide. The disease is characterised by the loss of retinal ganglion cells associated with a progressive optic neuropathy, resulting in an impairment of visual functions, for example, visual field loss. Nowadays, the only modifiable risk factor is the increase in intraocular pressure, and its treatment is to lower this pressure by medication, laser treatment or surgery to avoid disease progression. New methods for preventing and reversing vision loss are thus urgently needed. Several small and two multicentre studies have presented evidence that repetitive transorbital alternating current stimulation (rtACS) can lead to long-lasting visual field improvement. This could open a new and inexpensive therapeutic option for optic atrophy. However, the level of evidence for this method is still fairly rather poor, and further trials are needed. Therefore, this clinical trial aims to prove the effectiveness of rtACS compared with sham stimulation in patients with primary open-angle glaucoma (POAG).Methods and analysis VIRON (Vision Restoration in Optic Neuropathy) is a national, multicentre, prospective, randomised, placebo-controlled, double-blind trial with three arms. The primary objective is to assess the effectiveness of rtACS in patients with POAG compared with sham stimulation. The primary outcome is the change in mean defect (MD) in the visual field immediately after 10 sessions of rtACS (days 9, 16 and 23) compared with the values of initial perimetry (days −21 to –14 and 0) after applying electrical stimulation with a classical montage, compared with sham and electrical stimulation using individualised montage. Secondary outcome measures comprise a long-term effect with changes in MD at 24 weeks after stimulation, and data from the National Eye Institute Visual Function-25 and quality of life (Short Form 36) questionnaires. The target population are patients with glaucomatous optic atrophy and significant glaucomatous visual field defects (MD of 5–22 dB) due to POAG.After randomisation, patients received either classical rtACS (group 1), individual rtACS (group 2) or sham stimulation (group 3) in daily 25 min stimulation sessions in two series of five consecutive days separated by a weekend interval. In group 1, active stimulation will be via the routinely applied montage using two electrodes affixed on the right and left side of the head, next to the eyes, with straightforward fixation. In group 2, the current flow will be individually modelled (MRI-based) to target areas of partial visual field defects by optimising electrode positions in conjunction with an optimised visual fixation direction. Group 3 with sham stimulation will serve as control.The calculated sample size required to achieve a statistical power of 80% for a relevant effect size and allow for dropouts was 300 (100 per group). The trial has already begun with the first patient in July 2023. The planned recruitment period is 24 months with an estimated end of the study in November 2025 (last patient out). An adjusted extension of the study period is planned.Ethics and dissemination VIRON was approved by the Central Ethics Committee of the University Medical Center Göttingen (19 October 2022) and those of the individual participating centres (Bonn: 446/23-EP, Hamburg: 2023-200889-BO-bet, Cologne: 23-1487 and Mainz: 2023-17399-§23b). The study protocol complies with the Declaration of Helsinki, the national medicine device regulation (MDR) laws and the international standards of good clinical practice (GCP).The study protocol (V.5, 24 November 2023) was designed following the Standard Protocol Items: Recommendations for Interventional Trials guidelines and is registered on https://drks.de/search/de/trial/DRKS00029129.As study initiatior the University Medical Center Göttingen (UMG) is responsible for data ownership and data management of the VIRON study. The study data will be published within 6 months of the study being completed. After the publication of the primary results, all data are anonymised and published in an open-access journal to ensure access to the data for third parties.Trial registration number https://drks.de/search/de/trial/DRKS00029129.